2020
DOI: 10.1002/hed.26349
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes mellitus in major head and neck cancer surgery: Systematic review and meta‐analysis

Abstract: Background Diabetes mellitus (DM) is a risk factor for surgical complications and a common comorbidity in the setting of head and neck (H&N) cancer. Our objective was to determine if DM is associated with increased rates of H&N cancer surgery complications. Methods We conducted a search of Pubmed, Embase, and the national clinical trials database focusing on H&N cancer surgery or free flap reconstruction and diabetes. Two reviewers screened studies by title/abstract and then full text. We then collected data u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 43 publications
0
12
0
Order By: Relevance
“…4,5 Patients requiring reconstructive surgery often suffer from diabetes mellitus or peripheral vascular disease, that were shown to increase the rate of flap failure up to 4.5-fold. [6][7][8][9] This may lead to tissue necrosis and jeopardizes the reconstructive result. Necrosis can subsequently cause a series of events resulting in inflammation and further loss of tissue integrity.…”
Section: Introductionmentioning
confidence: 99%
“…4,5 Patients requiring reconstructive surgery often suffer from diabetes mellitus or peripheral vascular disease, that were shown to increase the rate of flap failure up to 4.5-fold. [6][7][8][9] This may lead to tissue necrosis and jeopardizes the reconstructive result. Necrosis can subsequently cause a series of events resulting in inflammation and further loss of tissue integrity.…”
Section: Introductionmentioning
confidence: 99%
“…Consisting of merely five studies, this analysis seemed relatively short of conclusiveness 38 . Further investigations were performed by Cupato et al 39 ; these authors www.nature.com/scientificreports/ www.nature.com/scientificreports/ www.nature.com/scientificreports/ www.nature.com/scientificreports/ gathered 16 studies for meta-analysis. They concluded that DM significantly increased flap failures and local region complications 39 .…”
Section: Discussionmentioning
confidence: 99%
“…Further investigations were performed by Cupato et al 39 ; these authors www.nature.com/scientificreports/ www.nature.com/scientificreports/ www.nature.com/scientificreports/ www.nature.com/scientificreports/ gathered 16 studies for meta-analysis. They concluded that DM significantly increased flap failures and local region complications 39 . This complication analysis was performed to include all major H&N surgeries instead of limiting the analysis to free-flap reconstructions 39 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dear Editor, We greatly appreciate Caputo et al 1 efforts in conducting a systematic review and meta-analysis to determine whether diabetes mellitus (DM) is associated with increased rates of head and neck (H&N) cancer surgery complications or not. Their results proved that DM was associated with increased rates of flap failure and local complications.…”
mentioning
confidence: 99%